Pengaruh AI Gemini Dan Nicemindmap Pada Hasil Belajar Pendidikan Agama Islam - Kusumawati; Ham Idris Tumenggung (Shofanah Media Berkah, 2026)
Religious education has so far focused more on cognitive theoretical religious issues, and has paid less attention to transforming cognitive religious knowledge into